Percampuran Deposito dan Investasi dalam Perspektif Fiqh Islam - Refky Fielnanda (Universitas Nurul Jadid, 2018)
Mudhâraba is partnership in profit between capital and work. It is conducted between investment account holders as owner of capital (rabb al-mâl) and the Islamic bank as a mudhârib. The Islamic bank announces its willingness, to accept the funds of invesment account holders, the sharing of profits being as agreed between the two parties, and the loss being borne by the owner of funds, unless they were due to misconduct, negligence or violation of the conditions agreed upon by the Islamic bank. A Mudhâraba contract may also be concluded between the Islamic bank, as a provider of capital on behalf of itself on behalf of invesment account holders, and bussiness owner.